Accumulation of Heavy Metals by Living and Dead Bacteria as Biosorbents: Isolated from Waste Soil - Andleeb, Saiqa; Batool, Iqra; Ali, Shaukat; Akhtar, Kalsoom; Ali, Nazish Mazhar (Biological Sciences - PJSIR, 2017)
In the present study Enterococcus luteus, Escherichia coli and Staphylococcus aureus have been used for biosorption of cadmium and chromium from aqueous solution of various concentrations. Bacteria were isolated from waste soil and identified through various morphological features, biochemical tests, and staining procedure. Biosorption capacity (both dead and live biomass) was observed through broth technique and absorbance values were measured using atomic absorbance spectrophotometer. Different parameters were optimised for metal biosorption, including incubation periods (24, 48, 72 and 96 h) and pH (4, 6, 7, 8, 9, and 10) at 37 °C. Agar well and agar disc diffusion methods were used for resistogram and antibiogram analysis. Through agar well diffusion method, S. aureus showed complete resistance against all concentrations of chromium and cadmium (50 to 300 µg/mL). E. luteus showed resistance on 50 µg/mL and 100 µg/mL of both metals while E. coli exhibited resistance against all cadmium concentrations (50 to 300 µg/mL) while sensitivity was observed in case of chromium (12.0 ± 0.0 mm to 24.0 ± 0.0 mm). Through broth method, E. luteus showed good cadmium absorbance capacity at acidic pH 4 and 6, E. coli at pH 4, 6 and 7 and S. aureus at pH 6, 7 and 8. In case of chromium, S. aureus showed maximum absorbance at pH 6; E. coli at pH 7 and 8 and E. luteus showed minimum absorbance for chromium at pH 6 and 8. All bacterial isolates showed maximum biosorption of both metals after 24 h of incubation. Results suggested that pH 6 and incubation period 24 h could be better for biosorption of cadmium and chromium removal. Dead biomass of E. coli and S. aureus was more efficient for cadmium removal while both dead and live biomass (E. luteus, E. coli and S. aureus) have potential for chromium removal. These microbes could be used as potential source of heavy metal biosorbent, biosorbent